Optimization of Ni(II) & Co(II) removal from wastewater and statistical studies on the results of experimental designs. Issue 2 (4th March 2019) - Igder, Aghil; Fazlavi, Ali; Allahkarami, Ebrahim; Dehghanipour, Ali
ABSTRACT: In this study, mono-dispersed carboxymethyl chitosan (CCS)-bounded Fe3 O4 (OCMCS/Fe3 O4 ) nanoparticles were used as a novel magnetic nano-adsorbent for the removal of Ni(II) and Co(II) ions from wastewater. Chitosan (CS) was first carboxymethylated and then covalently bounded on the surface of Fe3 O4 nanoparticles. The micrographs of the scanning electron microscopy analysis showed that the nanoparticles were mono-dispersed and had spherical morphology with mean diameter of 33 nm. X-ray diffraction patterns indicated that the magnetic nanoparticles were pure Fe3 O4 with a spinel structure, and the binding of O-CCS did not change the phase of Fe3 O4 . In this study, the most significant factors affecting adsorption process, i.e., pH, adsorbent dosage, contact time and concentration of Ni(II) and Co(II) ions were studied. Box–Behnken design and analysis of variance were used to determine the main effects and their interactions. The optimization study revealed that pH, adsorbent dosage and metal concentration had a significant effect on metal removal. In addition, results indicated that contact time parameter had no significant effect on the removal of Ni(II) and Co(II) ions ( p -value > 0.01).